Soil Analysis Software Tool for Smart Control of Agronomic Data - Satsyk, Viktor; Lishchyna, Nataliia; Khrystynets, Nataliia; Gumeniuk, Larysa; Korobchuk, Liudmyla (My University, 2022)
In this paper we develop system approach for obtaining, analysing and managing the agronomic parameters of the soil based on software and hardware IT-complex. The developed tool Soil Analysis Software Tool (S.A.S.T) is aasigned for measuring soil parameters with the possibility of integration into the system of research and online recommendations for optimization of consumables. Presented results makes a significant contribution to the concept of precision agriculture technic as farming IT model based on observing, control, detection regarding to inter and/or intra-field productive variability.
Keywords: Design Systems; Reliability; Smart Agriculture; Software Tool; Soil Analysis Software